Crenças de profissionais da política de assistência social em relação a questões raciais - Silva, Jéssica Fernandes da (Universidade Federal de São Carlos, 2024)
In the Brazilian context, the social services gained its government policy status with the Federal Constitution, published in 1988. The search for transversality to promote racial and gender equality in state public policies has always been a goal to be reached in this policy. Nevertheless, black people are still suffering from high levels of racial inequality and social vulnerability, which implies that this population becomes the main group assisted by the Brazilian National Policy of Social Services. Studies regarding the expression of racism have reported more subtle processes, indicating an alteration in the phenomenon. To this extent, it is relevant to better understand how racial beliefs are built by the professionals who work in this policy, given that the expression of racism may negatively affect black population. The aim of this research was to evaluate the manifestation of racial prejudice and racism in professionals who work in social services and its different expressions. Furthermore, the research aimed to describe the different profiles of professionals regarding to racial beliefs and how they are expressed. To this end, two quantitative, exploratory, descriptive, and cross-sectional studies were conducted with professionals based at the Brazilian National Policy of Social Services. Participated in the study 175 professionals, being 153 (87,4%) females and 22 (12,6%) males, aged 23-65 years old. The following questionnaires were employed: Brazil Criteria, Scale of Modern Racism and Scale of Subtle and Blatant Prejudice. Findings from Study 1 showed that only the Scale of Modern Racism had internal consistency and acceptable reliability. There were no statistically significant differences across the groups analyzed based on the results from the three scales. Moreover, the instruments used were not able to identify variations of expressions of racial prejudice and racism in the participants. Given the recognition that structural racism exists in the country and affects several societal levels, even in the public policies, the findings of this study suggest the need to further investigate if quantitative approaches, such as those which employed self-report items, are appropriate to investigate the phenomenon of racism and racial prejudice. In the second study, similar profiles were clustered based on their responses on the three scales used in the first study, aiming to identify similar variables of racism and racial prejudice. It was possible to find a cluster (n=7) where the average of racism and racial prejudice were higher than the other groups. Professionals from social services policy who have high rates of racial prejudice and racist are contributing to maintaining vulnerability conditions within the context of black population.. Given the challenges of researching this complex theme, and the limits of an adequate representativity with the number of participants of this research, we suggested that further analysis be developed in future by the integration of different methodological strategies, such as mixed-method studies approach.
Beliefs of professionals who work at the brazilian social assistance policy regarding racial issues
Keywords: PNAS; Preconceito sutil; Preconceito flagrante; Racismo moderno; Subtle prejudice; Blatant prejudice; Brazilian National Policy of Social Services; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL